Sense and stigma in the gospels : depictions of sensory-disabled characters - Lawrence, Louise Joy, 1975- (Oxford, United Kingdom : Oxford University Press, 2013)
The senses are used within New Testament texts as instruments of knowledge and power and thus constitute important mediators of cultural knowledge and experience. Likewise, those instances where sensory faculty is perceived to be "disabled" in some way also become key sites for ideological commentary and critique. However, often biblical scholarship, itself "disabled" by eye-centric and textocentric "norms," has read sensory-disabled characters as nothing more than inert sites of healing; their agency, including their alternative sensory modes of communication and resistance to oppression, remain largely unaddressed. In response, Louise J. Lawrence seeks to initiate a variety of interdisciplinary dialogues with disability studies and sensory anthropology in a quest to refigure characters with sensory disabilities featured in the gospels and provide alternative interpretations of their conditions and social interactions. In each instance the identity of those stigmatised as "other" (according to particular physiological, social and cultural "norms") are recovered by exploring ethnographic accounts which document the stories of those experiencing similar rejection on account of perceived sensory "difference" in diverse cross-cultural settings. Through this process these "disabled" characters are recast as individuals capable of employing certain strategies which destabilize the stigma imposed upon them and tactical performers who can subversively achieve their social goals. (Publisher)
Introduction: Sense and stigma -- Looking through a glass darkly : sensing disabilities of biblical studies -- Blind spots and metaphors : refiguring sightless characters in the gospels -- Sounding out a 'deaf-mute': Mark 7:31-37 as deaf world performance -- The stench of untouchability: sensory tactics of a leper, legion, and leaky woman -- Sense, seizures, and illness narratives: the case of an 'epileptic'/'demon-possessed, boy' -- Conclusion: 'Sensory-disabled' characters refiguring God.
Includes bibliographical references (pages 167-185) and indexes.
Keywords: Bible. -- Criticism, interpretation, etc; People with disabilities in the Bible; Senses and sensation in the Bible; People with disabilities -- Religious aspects -- Christianity; Sensory disorders -- Religious aspects -- Christianity; Senses and sensation -- Religious aspects -- Christianity; Other (Philosophy) in the Bible; Bible. Gospels - Criticism, interpretation, etc; People With Disabilities In The Bible